A SPATIAL PERSPECTIVE ON EUROPEAN INTEGRATION: HETEROGENEOUS WELFARE AND MIGRATION EFFECTS FROM THE SINGLE MARKET AND THE BREXIT. (10th October 2018) - Henkel, Marcel; Seidel, Tobias
Abstract : We use a quantitative model to study the implications of European integration for welfare and net migration flows across 1, 280 European regions. The model suggests that an increase of trade barriers to the level of 1957 reduces welfare by about 5%–8% on average, depending on the presumed trade elasticity. However, remote regions may face initial welfare losses of up to 10%. These heterogeneous welfare effects cause estimated net migration of 1.9% of the population to the European geographic center implying that the dismantling of trade barriers in Europe has led to a more homogeneous spatial distribution of economic activity. With regard to the Brexit, we find moderate welfare losses for the United Kingdom of 1.05% in the most pessimistic scenario while continental Europe's welfare declines by 0.41%. ( JEL F15, R12, R13, R23)